SIZE EFFECT OF COPPER NANOPARTICALS ON MICROCYSTIS AERUGINOSA - Kien, Nguyen Trung; Thu Huong, Tran Thi; Chau, Nguyen Hoai; Kim, Dang Dinh; Thuy, Duong Thi (Vietnam Journal of Biotechnology, 2018)
Cyanobacterial and toxins produced in cyanobacterial water blooms cause serious environmental problems which effects on freshwater ecosystems. The use of nanomaterials to control algal blooms is a new potential way for practical application due to its antibacterial as well as distinct physicochemical properties of nanomaterials. The particle size is one of the most determinant characteristics creating the different between nanomaterials and their larger bulk counterparts. However, size-dependent toxicity of nanoparticles has remained largely unknown. This study aimed to evaluate effect of three different nanoparticle sizes (d ≤ 10 nm; 30 nm ≤ d ≤ 40 nm and d ≥ 50 nm) on toxic cyanobacteria Microcystis aeruginosa. The copper nanoparticles were synthesized by electrochemical method and coated with chitosan to enhance the stability of materials in the water environment. The copper nanoparticle concentrations selected for toxic test were range from 0 (control); 0,01ppm; 0,05ppm; 0,1 ppm; 1ppm and 5 ppm. After ten days of experiment, the growth of M. aeruginosa was mainly affected at concentrations of 1 ppm and 5 ppm and there are no differences in inhibition between the particle sizes with efficiency of more than 80% in comparison to control. The highest toxicity of copper nanoparticles in M. aeruginosa was observed at particle size of 30 nm ≤ d ≤ 40 nm with EC50 = 0,73 ppm, which was respectively three to seven times less than the particle sizes of d ≥ 50 nm (EC50 = 2,62 ppm) and d ≤ 10nm (EC50 = 5,02 ppm) at the same time.